Images - Bakalchev, V., Tasic, S., Bakalchev, M. (My University, 2018)
The new architecture of the 1960 s and 1970 s is not only represented by the physical artifacts which redefined the basic postulates of the previous functionalist approach, but it also created a new visual basis for representing architecture. The images of that period of the work of Konstantinovski show and also highlight architecture as a constitutive, and at the same time as an autonomous architectural artifact.
Keywords: Konstantinovski, images, 1960 - 1970